Resistance Diagnostics in High-Voltage Circuits: From Design to Implementation - Lundkvist, Vera; Eriksson, Alice (My University, 2026)
In high voltage systems, marginal increases in contact resistance can trigger catastrophic overheating. This thesis aims to apply a product development framework to the challenge of resistance diagnostics within connectors and busbars for heavy-duty automotive applications. The research resulted in a dual-model diagnostic function designed to identify faults before critical temperature thresholds are reached. The first model utilizes a steady-state thermal equation to establish an expected maximum temperature based on applied current. The second model employs a predictive algorithm that analyzes current and the initial temperature derivative to estimate the actual projected peak temperature. By comparing the theoretical baseline with the predicted real-time peak, the system can detect abnormal resistance in its early stages. This approach enables detection of abnormal resistance in specific components, leading to rapid fault-tracing and enhancing the safety and reliability of heavy-duty electric powertrains
Keywords: High-voltage system; Resistance diagnostics; Product development